1981
DOI: 10.1002/pol.1981.180190213
|View full text |Cite
|
Sign up to set email alerts
|

Negative thermal expansion in oriented crystalline polymers

Abstract: Measurements on the thermal expansivity α∥ and α⟂ (along and normal to the draw direction, respectively) have been carried out for a series of oriented polymers with widely different crystallinities (0.36–0.81) and draw ratios (1–20) and over large temperature ranges covering the major amorphous transitions in each case. While α⟂ increases with temperature, α∥ tends to decrease sharply above the transition temperature. For highly crystalline polymers, α∥ decreases to values typical of polymer crystals (−1 × 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
83
1

Year Published

1982
1982
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(88 citation statements)
references
References 23 publications
4
83
1
Order By: Relevance
“…Experimental studies have shown that thermal expansion in oriented polymer fibers can be highly anisotropic [23,27]. Typically, oriented polymers show small expansions and sometimes contractions in the length direction on heating along with diameter direction expansion of significantly larger magnitude [27].…”
Section: Origin Of Anisotropic Volume Expansion In Oriented Polymer Fmentioning
confidence: 99%
See 3 more Smart Citations
“…Experimental studies have shown that thermal expansion in oriented polymer fibers can be highly anisotropic [23,27]. Typically, oriented polymers show small expansions and sometimes contractions in the length direction on heating along with diameter direction expansion of significantly larger magnitude [27].…”
Section: Origin Of Anisotropic Volume Expansion In Oriented Polymer Fmentioning
confidence: 99%
“…Typically, oriented polymers show small expansions and sometimes contractions in the length direction on heating along with diameter direction expansion of significantly larger magnitude [27]. Thermal contraction in the fiber length direction has been attributed to contributions from both crystalline and non-crystalline regions in the oriented fiber [27].…”
Section: Origin Of Anisotropic Volume Expansion In Oriented Polymer Fmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in addition to them, the other factors, iPP crystal orientation 9) and the tie molecules pulled out from the iPP crystalline region 26,27) will also be deeply connected with this anisotropic CLTE phenomenon. We will now carry out the analysis of the CLTE anisotropy by introducing these factors together with the TEMT results obtained in this study.…”
Section: Correlation Of Clte Anisotropy With Irregularities In the Eomentioning
confidence: 99%